Determining The Indicators of Sustainability to Be Achieved in New Cities and Urban Communities (International Journal of Scientific Research and Management (IJSRM), 2023)
Indicators are one of the effective mechanisms for achieving and measuring the targeted progress of urban communities at their different levels towards the desired and planned results for development, and to determine the indicators of sustainability to be achieved in new cities and urban communities. Some sustainability rating systems for residential neighborhoods in different countries will be studied, as well as the Egyptian Rating System (Gprs). And extracting the most important indicators and determinants of sustainability that you use to evaluate buildings and residential neighborhoods, as well as studying some other aspects that help to reach the sustainability indicators that are required to be achieved at the city level, and through this, the most important sustainability indicators will be reached and limited as basic indicators for achieving and measuring sustainability in new cities and urban communities, and it is possible to add or delete Indicators, including according to the nature of the cities (tourist - industrial – coastal-….) .